2021
DOI: 10.1029/2021gl092436
|View full text |Cite
|
Sign up to set email alerts
|

Caldera Collapse as the Trigger of Chaos and Fractured Craters on the Moon and Mars

Abstract: Introduction Chaotic TerrainsChaotic terrains are broad regions on Mars, often depressed and bordered by scarps, where the bedrock is characterized by large irregular mesas arranged chaotically (Sharp, 1973). Toward the inner part of the chaos, the mesas evolve into more and more eroded knobs. In some areas, hydrated minerals were found in the overlying light-toned layered deposits (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…The results presented here corroborate other studies that advocate a late magmatic insurgence in the Ladon basin. Following the experimental results obtained by Luzzi et al (2021), the general radial and concentric distribution of grabens centered at the western part of the basin, as well as their T and Y-shaped junctions, would testify to such a late magmatic activity causing oblate extension and diffused fissure eruptions. Similarly, the abundance of FFCs in the close vicinity of the East Ladon study area (Figure 2) would testify to the nearby emplacement of magmatic bodies, whether sills or laccoliths, which could share a common magmatic source with Units 1-3 in this work.…”
Section: Listwanitization In the Regional Frameworkmentioning
confidence: 78%
See 2 more Smart Citations
“…The results presented here corroborate other studies that advocate a late magmatic insurgence in the Ladon basin. Following the experimental results obtained by Luzzi et al (2021), the general radial and concentric distribution of grabens centered at the western part of the basin, as well as their T and Y-shaped junctions, would testify to such a late magmatic activity causing oblate extension and diffused fissure eruptions. Similarly, the abundance of FFCs in the close vicinity of the East Ladon study area (Figure 2) would testify to the nearby emplacement of magmatic bodies, whether sills or laccoliths, which could share a common magmatic source with Units 1-3 in this work.…”
Section: Listwanitization In the Regional Frameworkmentioning
confidence: 78%
“…For this reason, similar to the Moon (Jozwiak et al, 2014), magma intrusion and subsequent crater floor uplift might be a cause for FFC formation even in the absence of groundwater or ice (Bamberg et al, 2014). Luzzi et al (2021) suggested that FFC fracturing could result from a succession of magmatic inflation and deflation episodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016) found that more segmented faults show a lower D max / L ratio, while individual fault segments accumulated more displacement for a given fault length, and this could be due either to an advanced maturity in the fault's evolution or to the fact that such fault grew in isolation and had no chances of linkage; Finally, in case where the fault experiences a reactivation in the opposite sense of slip (and this would be the case if we assume both the inflation first proposed by P. H. Schultz (1976), and the piecemeal caldera collapse suggested by Luzzi et al. (2021)), reverse faults reactivated as normal can show lower values of D max / L ratios (Kim & Sanderson, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Several types of terrains and thus landforms are peculiar to specific areas or even planets or moons. For instance, Chaotic Terrains are planetary surface features notably found on Mars, Mercury, Jupiter's moon Europa and Pluto (Luzzi et al, 2020(Luzzi et al, , 2021Skjetne et al, 2021). Mountains, hills, plains volcanoes are common in almost all rocky planets of the Solar System (Hargitai & Kereszturi, 2015).…”
mentioning
confidence: 99%